2017
DOI: 10.1152/ajpendo.00447.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on compensatory pancreatic β-cell hyperplasia in mice fed a high-fat diet

Abstract: Metformin has been widely used for the treatment of type 2 diabetes. However, the effect of metformin on pancreatic β-cells remains controversial. In this study, we investigated the impacts of treatment with metformin on pancreatic β-cells in a mouse model fed a high-fat diet (HFD), which triggers adaptive β-cell replication. An 8-wk treatment with metformin improved insulin resistance and suppressed the compensatory β-cell hyperplasia induced by HFD-feeding. In contrast, the increment in β-cell mass arising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…It was important to investigate whether metformin‐induced improvement of hippocampal deterioration in middle‐aged DIO mice is involved in recovery from type 2 diabetes. Previous studies have shown that long‐term metformin treatment has no effect on body weight or blood glucose levels in HFD‐fed mice . Consistent with these results, prolonged treatment with metformin failed to improve weight gain, elevated levels of fasting blood glucose, and feeding behavior in middle‐aged DIO mice (Fig.…”
Section: Resultssupporting
confidence: 80%
“…It was important to investigate whether metformin‐induced improvement of hippocampal deterioration in middle‐aged DIO mice is involved in recovery from type 2 diabetes. Previous studies have shown that long‐term metformin treatment has no effect on body weight or blood glucose levels in HFD‐fed mice . Consistent with these results, prolonged treatment with metformin failed to improve weight gain, elevated levels of fasting blood glucose, and feeding behavior in middle‐aged DIO mice (Fig.…”
Section: Resultssupporting
confidence: 80%
“…In addition, long-term exposure to FFA results in suppressed glucose-stimulated insulin secretion (GSIS) and reduced insulin biosynthesis [ 72 ], eventually leading to adaptive decline of β-cell mass and/or function as a compensatory response to insulin resistance. Chronic glucose and fatty acid exposure eventually result in β-cell failure and the development of diabetes [ 72 , 73 ].…”
Section: Metformin Improves Pancreatic β-Cell Functionmentioning
confidence: 99%
“…The effect of metformin on high-glucose-induced pancreatic β-cell hyperplasia remains controversial. HFD-triggered adaptive pancreatic β-cell replication was suppressed by eight weeks of metformin treatment [ 73 ]. However, after sixty weeks of HFD feeding, increased β-cell mass was not suppressed [ 73 ].…”
Section: Metformin Improves Pancreatic β-Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on rats proved that metformin, by decreasing oxidative stress in pancreatic islets, might have a direct beneficial effect on insulin secretion [89]. It improves insulin resistance and suppresses the compensatory β-cell hyperplasia induced by high-fat diet [90], therefore it might reduce visceral fatty tissue.…”
Section: Promising Results For Drug-based Therapiesmentioning
confidence: 99%